Desarrollo del gametofito de Pteris berteroana (Pteridaceae: Pterideae) - Mendoza, Aniceto (1996)
The development and characteristics of the sexual phase of Pteris berteroana, endemic to the Archipielago Juan Femandez, Chile, are reported. Spore gennination is of the Vittaria-type, resulting in a uniseriate gametophytic filament of three to five ceUs. Prothallial development is of the Ceratopteris-type, by the development of a meristematic lateral lOne, the young prothallus is asymmetric with unequal wings. The prothallia reaches sexual maturity in 120- ISO days. The gametangia are of (he common leptosporangiate-type. Sporophyte development was observed. The described morphogenetic characteristics of P. berteroana such as types of gennination, prothallial development and gametangia, as well as the cordiform thallus, are evolutionarily derived ("advanced") characters shared by several groups of homosporic fems.